Effectiveness Model Of Leadership, Business Environment and Organizational Work Culture On The Implementation Of Corporate Governance (GCG) In BPR In DKI Jakarta - Puspitasari, Devy Mawarnie; Rosdiana, Riska; Dasman, Sunita; Rahayu, Piki; Kusuma, Spaikurahman (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
This research aims to establish a model of leadership effectiveness, business environment and organizational work culture on the implementation of corporate governance (GCG) in BPR in DKI Jakarta. The data collection method uses a survey method with the research instrument being a questionnaire. The data analysis method used in this research is the Structural Equation Model (SEM) – Partial Least Square (PLS) with the Smart-PLS analysis tool. The population used in this research was BPR in DKI Jakarta and the sample size was determined using a saturated sampling technique. The research results show that leadership, business environment and organizational work culture have a significant influence on corporate governance. Therefore, BPR must pay attention to variables that are indicators of good GCG practices to support the achievement of company performance targets. This research contributes to producing a model that is able to explain 81% of GCG implementation for banking in Indonesia, especially BPR.